Sodium-mediated plateau potentials in an identified decisional neuron contribute to feeding-related motor pattern genesis in Aplysia - Bédécarrats, Alexis; Simmers, John; Nargeot, Romuald (Frontiers in Neural Circuits, 2023)
Motivated behaviors such as feeding depend on the functional properties of decision neurons to provide the flexibility required for behavioral adaptation. Here, we analyzed the ionic basis of the endogenous membrane properties of an identified decision neuron (B63) that drive radula biting cycles underlying food-seeking behavior in Aplysia. Each spontaneous bite cycle arises from the irregular triggering of a plateau-like potential and resultant bursting by rhythmic subthreshold oscillations in B63’s membrane potential. In isolated buccal ganglion preparations, and after synaptic isolation, the expression of B63’s plateau potentials persisted after removal of extracellular calcium, but was completely suppressed in a tetrodotoxin (TTX)- containing bath solution, thereby indicating the contribution of a transmembrane Na+ influx. Potassium outward efflux through tetraethylammonium (TEA)- and calcium-sensitive channels was found to contribute to each plateau’s active termination. This intrinsic plateauing capability, in contrast to B63’s membrane potential oscillation, was blocked by the calcium-activated non-specific cationic current (ICAN) blocker flufenamic acid (FFA). Conversely, the SERCA blocker cyclopianozic acid (CPA), which abolished the neuron’s oscillation, did not prevent the expression of experimentally-evoked plateau potentials. These results therefore indicate that the dynamic properties of the decision neuron B63 rely on two distinct mechanisms involving different sub-populations of ionic conductances.